Gender Bias and Artificial Intelligence: A Challenge within the Periphery of Human Rights - Prashant Chauhan; Gagandeep Kaur (Hasanuddin Law Review, 2022)
Technology is advancing at an exponential rate, and artificial intelligence has become a contentious issue of the day. A plethora of fields influencing human life has been impacted by artificial intelligence, whereas the development of artificial intelligence has opened Pandora’s box of legal concerns. Several international organizations, including the United Nations, have identified gender equality as an indispensable constituent of the protection of human rights. The voyage of gender equality has seen a long phase of struggle and persists. This paper aims to analyze, in what manner artificial intelligence is affecting gender equality, raising concerns on the issues regarding the role played by the United Nations in securing gender equality through conventions and resolutions, is artificial intelligence capable of posing a threat to gender equality and what measures can be implemented to secure gender equality about artificial intelligence.